Stratégies paysannes pour la protection du maïs indigène dans l'État de Tlaxcala - Pánfilo Hernández Ortiz (Revue d'ethnoécologie)
The article presents the strategies deployed by the Vicente Guerrero Group in Tlaxcala to prevent the use of transgenic corn in the region, as well as to revitalize the use of native varieties of corn. It also shows the history of the group in question and the itineraries followed by the nucleus of peasant promoters from the 1990s until the approval of the “Law for the promotion and protection of corn as original heritage, in constant diversification and food for the state of Tlaxcala” in 2011. Based on these elements, we discuss the importance of both the legal defense of cultivated diversity, and the social actions that help in the in situ conservation of native varieties.